HOME-BASED CARE MODEL AS A COST-EFFECTIVE STRATEGY FOR REDUCING HOSPITALIZATION IN PATIENTS WITH NONCOMMUNICABLE DISEASES (World Bulletin of Public Health, 2026)
To evaluate the clinical effectiveness and cost-effectiveness of a structured nursing-led home-based care model in reducing hospitalization among patients with chronic NCDs.
Keywords: noncommunicable diseases; home-based care; cost-effectiveness